Copy number variation in Han Chinese individuals with autism spectrum disorder - Gazzellone, Matthew J (BioMed Central, 2014)
BACKGROUND: Autism spectrum disorders (ASDs) are a group of neurodevelopmental conditions with a demonstrated genetic etiology. Rare (<1% frequency) copy number variations (CNVs) account for a proportion of the genetic events involved, but the contribution of these events in non-European ASD populations has not been well studied. Here, we report on rare CNVs detected in a cohort of individuals with ASD of Han Chinese background. METHODS: DNA samples were obtained from 104 ASD probands and their parents who were recruited from Harbin, China. Samples were genotyped on the Affymetrix CytoScan HD platform. Rare CNVs were identified by comparing data with 873 technology-matched controls from Ontario and 1,235 additional population controls of Han Chinese ethnicity. RESULTS: Of the probands, 8.6% had at least 1 de novo CNV (overlapping the GIGYF2, SPRY1, 16p13.3, 16p11.2, 17p13.3-17p13.2, DMD, and NAP1L6 genes/loci). Rare inherited CNVs affected other plausible neurodevelopmental candidate genes including GRID2, LINGO2, and SLC39A12. A 24-kb duplication was also identified at YWHAE, a gene previously implicated in ASD and other developmental disorders. This duplication is observed at a similar frequency in cases and in population controls and is likely a benign Asian-specific copy number polymorphism. CONCLUSIONS: Our findings help define genomic features relevant to ASD in the Han Chinese and emphasize the importance of using ancestry-matched controls in medical genetic interpretations.